1987
DOI: 10.3171/jns.1987.66.1.0040
|View full text |Cite
|
Sign up to set email alerts
|

Use of detachable balloons for proximal artery occlusion in the treatment of unclippable cerebral aneurysms

Abstract: Of 68 patients with unclippable aneurysms treated by proximal artery occlusion with detachable balloons, permanent occlusion was achieved in 65; of these patients, 37 had carotid artery aneurysms below the origin of the ophthalmic artery, 21 had aneurysms arising from the supraclinoid portion of the carotid artery, six had basilar trunk aneurysms, and one had a distal vertebral aneurysm. Examination for treatment selection included assessment of the circle of Willis by compression angiography and xenon blood f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
95
0
1

Year Published

1992
1992
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 374 publications
(96 citation statements)
references
References 10 publications
0
95
0
1
Order By: Relevance
“…Data from the era of surgical ICA clamp occlusion without previous tolerance testing indicate that approximately three-fourths of patients can tolerate ICA occlusion. [16][17][18] In our cohort, the angiographic test indicated tolerance to permanent ICA occlusion in two-thirds of patients, which indicates that the proportion of false-negatives is probably limited. After ICA occlusion, all aneurysms thrombosed completely except one, which makes the treatment very effective.…”
Section: Discussionmentioning
confidence: 79%
“…Data from the era of surgical ICA clamp occlusion without previous tolerance testing indicate that approximately three-fourths of patients can tolerate ICA occlusion. [16][17][18] In our cohort, the angiographic test indicated tolerance to permanent ICA occlusion in two-thirds of patients, which indicates that the proportion of false-negatives is probably limited. After ICA occlusion, all aneurysms thrombosed completely except one, which makes the treatment very effective.…”
Section: Discussionmentioning
confidence: 79%
“…[21][22][23] However, with the availability of intracranial stents, these aneurysms can now safely be treated with sparing of the parent vessel, and parent vessel occlusion techniques are hardly ever indicated for these aneurysms.…”
Section: Vertebral Artery Occlusionmentioning
confidence: 99%
“…Eighty of 82 petrous and cavernous aneurysms were obliterated with proximal occlusion, only 4 of which required trapping. In 1987, Fox et al 3 reported 58 patients with anterior circulation giant aneurysms, with all 37 aneurysms below the ophthalmic segment and 10 of 21 supraclinoid aneurysms obliterated with proximal occlusion alone without the need for trapping. We have been unable to find evidence in the literature demonstrating the inferiority of proximal occlusion as a first-line procedure.…”
mentioning
confidence: 99%